Midline Astrocytic Tumors in Children: A Retrospective Study of 152 Cases - Prasad, Hanuman; Kumar, Raj; Faheem, Mohd (Journal of Pediatric Neurology, 2020)
The aim of this study was to analyze the various midline structures having preponderance for astrocytoma, their incidence, clinical features, operative approach, prognosis, and outcomes in children. It is a retrospective analysis of 152 cases with midline astrocytic tumors in children admitted between January 1995 and December 2012 in the Department of Neurosurgery at Sanjay Gandhi Postgraduate Institute of Medical sciences Lucknow, India. The mean age of the cases with midline astrocytic tumors was 9.29 ± 4.56 years. Majority of these tumors occurred in the age group of 6 to 10 years (n = 58, 38.16%), with male to female ratio being 1.66:1. Out of 152 cases, tumors located at midline cerebellum constituted majority of the cases (n = 38, 25%) followed by brain stem (n = 28, 18.42%), thalamic region (n = 24, 15.79%), corpus callosum (n = 18, 11.82%), pineal region (n = 12, 7.89%), optic nerve (n = 12, 7.89%), chiasmo-hypothalamic (n = 10, 6.58%), and septum pellucidum astrocytomas (n = 10, 6.58%). Majority of these tumors were of low-grade type (n = 136, 89.47%), and pilocytic astrocytomas were the commonest subtypes. Out of 152 cases, 136 (89.47%) cases had improved outcomes, 8 (5.26%) remained as they were in preoperative state, and mortality was seen in 8 (5.26%) of the cases at 3 to 77 months (mean 26.70 ± 9.70) of follow-up. Midline structures having preponderance for astrocytomas were midline cerebellum, brain stem, thalamus, corpus callosum, pineal region, optic nerve, chiasmo-hypothalamic, and septum pellucidum. Cerebellum was the commonest site. Most of these astrocytomas were of low grade with pilocytic astrocytoma being the commonest subtype. With meticulous presurgical planning, most of these tumors have good outcome with significant reduction in mortality and morbidity.
Keywords: Midline; astrocytoma; histopathology; children; distribution; outcomes